Tuberculosis of symphysis pubis in a 17 year old male: a rare case presentation and review of literature - Bali, Kamal (BioMed Central, 2010)
Tuberculosis of symphysis pubis is a rare condition with hardly any report of such cases in the last decade. It is necessary to distinguish the entity from more common ones like Osteitis pubis and Osteomyelitis of pubis symphysis by urgent means in order to start the treatment early and thereby minimize morbidity and prevent complications. A rare case of tuberculosis of symphysis pubis in a 17 year old male is described. A high index of suspicion along with an extensive workup including 3-phase bone scan and fine needle aspiration led to the diagnosis. The patient had an excellent outcome following a complete course of multidrug chemotherapy for tuberculosis.